Post Kala Azar Dermal Leishmaniasis (PKDL) Presenting with Ulcerated Chronic Paronychia Like Lesion - Jha, AK; Anand, V; Mallik, SK; Kumar, P (Kathmandu University Medical Journal, 2014)
A 50-year-old lady, resident of urban Bihar, presented with inflamed proximal nail fold of a single digit for one and half months. The lesion on distal finger was remarkable for ulceration. Mucocutaneous examination revealed multiple hypopigmented macules and patches, notable for absence of scaling. The presence of ulceration was not consistent with chronic paronychia, hence, she was asked for biopsy. She declined and opted for trial of antibiotic and anti-fungal treatment. At two weeks of follow up, no improvement was noted at all. At the same time, she developed multiple juicy papules in perioral area and on neck. She tested positive by rK 39 tests. Histopathology from periungual area showed LD body. She was diagnosed as Post Kala-azar dermal leishmaniasis and was treated with miltefosine 50 mg twice daily for three months, resulting in complete resolution of all lesions. DOI: http://dx.doi.org/10.3126/kumj.v10i4.11010 Kathmandu Univ Med J 2012;10(4):87-90